The effectiveness of life insurance sales force training: Welcome 'me and AI' - Andrzej Janowski (Economies, 2025)
After 35 years of a free market in Poland, three life insurance companies have gained a dominant position in the market and developed certain procedural equilibrium in the area of training, allowing their status quo to be maintained. Yet, they do not take into account the opinions of agents and the possibility of using the latest IT developments, including artificial intelligence, which supports increasingly broad areas of activity in organisations with great success. As independent sales force training poses a challenge to any national or multinational company in a constantly changing global economy, the primary focus of this research was to analyse the opinions of the top 438 agents from dominant life insurance companies. A need was emphasised to reconfigure the existing training programmes with the potential for AI involvement to achieve a more effective educational trajectory. The research findings confirmed the necessity to reconstruct training programmes in relation to an agent's age, education level, and seniority and offered grounds for discussing innovative AI concepts that can be relevant for future academic research in management sciences and improving organisational effectiveness, particularly in life insurance companies or other first-contact personnel-dependent institutions.
Keywords: 330; agent; human performance; life insurance; sales effectiveness; organisational performance